Given a = 3 and b = - 8 ,
= > 2b² - 4a + 4a²
= > 2( - 8 )² - 4( 3 ) + 4( 3 )²
= > 2( 64 ) - 4( 3 ) + 4( 9 )
= > 128 - 12 + 36
= > 116 + 36
= > 152
Answer:
12x the second -12x -16
Step-by-step explanation:
Solving systems of equations with 3 variables is very similar
The second one is bigger as the square is a even number with the negative whole
The simplified form of the expression is given as 83x/56 -(97/105)
<h3>Finding the value of unknown variables</h3>
Alphabets are usually represented as unknown variables in a equation or expression.
Given the following expression shown below
6/7 x -2/3 + 3/5 + 5/8 x -6/7
Collect the like terms to have;
6/7 x+ 5/8 x -2/3 + 3/5 -6/7
Simplify
48x+35x/56 - (70-63 + 90)/105
The final expression will be given as;
83x/56 -(97/105)
Hence the simplified form of the expression is given as 83x/56 -(97/105)
Learn more on expression simplification here: brainly.com/question/723406
#SPJ1
Error error error error error error error